(untitled) (Research, Society and Development, 2022)
Aim: To assess and compare the inflammatory infiltrate, area of muscle cells, microvessel density (MVD) and expression of cytokines in the myocardium (MM) and lingual (LM) musculature between chagasic and non chagasic individuals. Methods: Fragments of MM and LM from autopsied chronic chagasic (CC) (n=18) and non chagasic individuals (n=24) were histologically processed for histochemical and immunohistochemical evaluation. Was assessed the MVD by CD31 and quantification of immune cells infiltrated in MM and LM, and also expression of IL-1, IL-10 and TGF- β1. Results: There were higher intensity of inflammation and larger area of muscle cells in the myocardium and tongue of chagasic compared to non-chagasic individuals (p<0.0001). In the chagasic individuals, there was a positive correlation: regarding to the MVD between the LM and MM (p=0.049); between area of MM and density of leukocytes expressing TGF-β1 (p=0.049); and IL-10 correlate with the MM and LM (p=0.029). Conclusions: The correlation between the density of leukocytes immunostained by anti-TGF-β1 and hypertrophy in the myocardium suggests the participation of this cytokine in cardiac muscle hypertrophy. Moreover, the hypertrophy in the myocardium and lingual muscles, and the concomitant expression of CD31 and IL-10 between the myocardium and lingual musculature in chagasic individuals suggests that evaluation of the tongue musculature presents certain similarities changes as a myocardium muscle in CC. However, it needs more studies to verify in other phases of the disease, if the parasite is installed in the tongue or if the mechanisms are reflex of systemic changes in level of immune response.